Analyzing DWT and IWT Techniques for Fitness Evaluation in Watermarking Technique Imperceptibility Performance for Medical Images - Abdullad, Maryam J.; Ismail, Amelia Ritahani; Abubakar, Adamu (2020)
Image watermarking techniques applied frequency transmission technique to improve the imperceptibility, robustness, and embedding capacity performance. For the medical image, the watermarking technique gives the imperceptibility performance priority for the importance of the visual quality of the medical image in medical diagnose. The fitness evaluation method involved in the process of watermark data embedding to control the level of imperceptibility performance. DWT and IWT are most Wavelet transmission techniques used in the proposed watermarking techniques. In this paper, a comparison between the DWT and IWT was conducted to analyze the performance of both transforms in terms of image visual quality and embedding capacity.